Growth curve fitting and analysis of intestinal flora changes of the Magang Goose (Anser domesticus) during 1 to 70 days post hatch - Li, X.; Song, G.; Cao, Q.; Mo, Q.; Fu, Y.; Chen, J.; Lukuyu, Ben A.; Wang, S.; Ye, H.; Zhu, Y.; Muhammad, K.S.; Yang, L.; et al. (Elsevier, 2025)
Nonlinear models are frequently utilized to study the growth and development of livestock and poultry, and to investigate the dynamic relationship with the intestinal microbiota changes. In this study, a total of 180 Magang geese (1-day-old) were selected and randomly divided into 6 replicates with 30 geese in each replicate. The growth performance, organ development, and intestinal flora composition of geese aged 7, 14, 21, 28, 42, 50, 60, and 70 d were observed. A total of 3 nonlinear growth models were applied to fit the development curves, aiming to explore the ontogenic development of Magang geese and the dynamic changes in the intestinal flora. Our results demonstrated that the Gompertz model serves as the most suitable model for simulating the growth pattern of Magang geese (R2=0.996). Using this model, the weight of the inflection point in Magang geese was 3.470 kg, the age of the inflection point was 25.460d, and the maximum daily gain was 0.061 kg. The development curves of the liver, kidney, and pancreas conform to the Logistic model (R2=0.901, 0.978, 0.971), while the intestinal development also followed this model. The bacteria involved in energy metabolism (Subdoligranulum, Bacteroides, Romboutsia) and the bacteria inhibiting the colonization of harmful bacteria (Blautia) in cecum changed rapidly from 7 to 14 d, and microbial community composition stabilized after 21 d. In conclusion, our findings indicated that the ontogenic pattern of the Magang goose conformed to the Gompertz growth curve. The period from 7 to 42 d represents the rapid growth phase for Magang geese, during which organ development occurs, and cecal microbiota composition becomes increasingly stable.